Crisis in accounting education / Nur Fakhzan Marwan - Marwan, Nur Fakhzan (Universiti Teknologi MARA Cawangan Pahang, 2002)
The perceived deficiencies in accounting education have prompted widespread calls from interested stakeholders, such as accounting educators, practitioners, and employers, with increased emphasizes on developing communication, interpersonal and intellectual skills, and on broadening the knowledge base in accounting education. This paper explores the effects of business changes, which have brought tremendous change to accounting profession, and eventually have led to crises in accounting education. The roles of education and universities then are examined, follow by discussion of whether the increased length of education is justified, and should students complete more liberal arts studies in their accounting degree. Finally, some prospects for accounting education changes are considered.